Simultaneous gas-chromatographic urinary measurement of sugar probes to assess intestinal permeability: use of time course analysis to optimize its use to assess regional gut permeability - Shaikh, Maliha (Clin Chim Acta, 2015)
BACKGROUND: Measurement of intestinal permeability is important in several diseases but currently several methods are employed. We sought to: (1) develop a new GC based method to measure urinary mannitol, lactulose and sucralose to assess regional and total gut permeability; (2) analyze the kinetics of these sugars in the urine to determine which ratio is useful to represent intestinal permeability; and (3) determine whether age, gender, race and BMI impact these values. METHODS: Subjects drank a cocktail of sucrose, lactulose, mannitol and sucralose and these sugars were measured in the urine at 5, 12 and 24 h with gas chromatography. RESULTS: Urinary mannitol exhibited significantly different kinetics than lactulose and sucralose which were similar to each other and varied little over the 24 h. No permeability differences were observed for renal function, age, race, sex, or BMI. CONCLUSIONS: Our data do not support the use of the widely used L/M ratio as an accurate estimate of intestinal permeability. Our data support the use of: The sucralose/lactulose (S/M) ratio to measure: small intestine permeability (first 5 h); small and large intestine (first 12 hours), and total gut permeability (24 h). This was also found to be true in a Parkinson’s disease model.